Effects and mechanism of graphene-structured biochar on maize growth and soil amelioration: A case study in loess plateau - Li, Bowen; Lai, Xingyang; Mao, Xiaofei; Xiong, Yang; Li, Gang; Zhao, Nan; Xie, Bo (International Journal of Agricultural and Biological Engineering, 2026)
Land improvement technology effectively addresses the challenges of arable land shortages, soil degradation, and the food crisis. Graphene-structured biochar (G-biochar) emerges as a promising soil conditioner among the innovative solutions due to its unique properties and lower cost. This study conducted field experiments to monitor and evaluate soil quality recovery at various maize growth stages in loess. The results indicate that the lamellar structure of G-biochar enhances soil aggregation, reduces water evaporation, and increases soil moisture content by 17.6% compared to the control. Due to the interactions with cations through delocalized π electrons, G-biochar leads to the enrichment of nitrogen cations and adsorption of phosphate, specifically, the concentration of nitrate nitrogen and available phosphorus improved by 25.0% and 178%, respectively. The maize treated with G-biochar has a higher yield, nutrition, and germination rate. Additionally, G-biochar demonstrates remarkable performance in altering the abundance and composition of soil microbial communities. G-biochar significantly improves soil moisture content, quality, nutrient utilization, and modulates the soil microbiome in the test loess plateau, it may be used as a promising soil conditioner. This research provides a case analysis of G-biochar’s impact on the maize-loess system. It explores the mechanisms underlying its function as a soil conditioner, offering theoretical support for its application in land improvement strategies. Key words: graphene-structured biochar; maize-loess system; nutrient utilization; microbial communities; soil moisture retention DOI: 10.25165/j.ijabe.20261904.10537 Citation: Li B W, Lai X Y, Mao X F, Xiong Y, Li G, Zhao N, et al. Effects and mechanism of graphene-structured biocharon maize growth and soil amelioration: A case study in loess plateau. Int J Agric & Biol Eng, 2026; 19(4): 143–151.